Математична модель теплового стану потужного гідрогенератора-двигуна - Грубой, О.П.; Федоренко, Г.М.; Кенсицький, О.Г. (Технічна електродинаміка, 2012)
The mathematical model of the thermal state of hydro generator-motor of Dniester HPSPP is worked out. The calculations of heating of basic elements of stator and rotor are conducted in the different modes of loading of machine. They got results are confronted with data of thermal tests of hydro generator-motor. The ways of increase of reliability and loading ability of aggregate are offered.